(Social) media isn’t the message, networked people are: calls for protest through social media - Lapa, T.; Cardoso, G. (Observatorio (OBS*), 2016)
In recent years, protests took the streets of cities around the world. Among the mobilizing factors were the perceptions of injustice, democratization demands, and, in the case of liberal democracies, waves of discontentment characterized by a mix of demands for better public services and changes in the discredited democratic institutions. This paper discusses social media usage in mobilization for demonstrations around the world, and how such use configures a paradigmatic example of how communication occurs in network societies. In order to frame the discussion, social media appropriation for the purposes of political participation is examined through a survey applied online in 17 countries. The ways in which social media domestication by a myriad of social actors occurred and institutional responses to demonstrations developed, it is argued that, in the network society, networked people, and no longer the media, are the message.